Pelatihan Literasi Numerasi untuk Mendukung Pembelajaran Matematika Kontekstual pada Siswa - Nasruddin, Nasruddin; Miftachurohmah, Nisa; Jahring, Jahring; Sari, Dian Ulfa (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
The contextually-based numeracy literacy instruction aimed to improve students' capacity to comprehend and utilize mathematical ideas pertinent to everyday life. Numeracy literacy is a crucial competency in contemporary society; nevertheless, polls reveal that pupils' numeracy abilities in Indonesia are still comparatively inadequate. This program offered training for educators and learners to adopt a contextually-based learning methodology. The understanding test results indicated a rise in students' average scores from 51.18 in the pre-test to 81 in the post-test, so validating the efficacy of this method. Furthermore, educators acquired novel perspectives on contextual teaching methodologies, enhancing the engagement and relevance of mathematics education. Periodic assessments indicated that students instructed by this strategy attained superior learning outcomes relative to traditional methods. The documentation of best practices functions as a reference for other schools to implement analogous strategies. This program markedly enhances the quality of mathematics education.